PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR METEMATIKA SISWA KELAS VII A MTs HUBBULWATHAN DURI - Novika Sari; Zulkarnain Zulkarnain; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to improve the learning process and learning outcomes math class VII A Hubbulwathan MTs Duri by applying Cooperative learning model Numbered Heads Together (NHT) type. The subjects were students of class VII A with heterogen academic ability. This research is a class action with two cycles. Each cycle has four steps, the steps are the planning, implementation, observation and reflection. Results showed activity sheets and teacher observation of students have done well after taking action. There is an improvement in the students learning process and an increase in the number of students who achieved at UH minimum completeness criteria end of each cycle compared to the number of students who achieve minimum completeness criteria on base score. The results of this study indicate that the application of cooperative learning model Numbered Heads Together (NHT) can improve the process of learning and improving mathematics learning outcomes of VII A Student in the MTS Hubbulwathan Duri on first semester of academic year 2013/2014. Key words: Mathematics Learning Outcomes, Cooperative Learning, Numbered Head Together (NHT), Classroom Action Research.